Contribution of physician assistants/associates to secondary care: a systematic review. Issue 6 (19th June 2018) - Halter, Mary; Wheeler, Carly; Pelone, Ferruccio; Gage, Heather; de Lusignan, Simon; Parle, Jim; Grant, Robert; Gabe, Jonathan; Nice, Laura; Drennan, Vari M
Abstract : Objective: To appraise and synthesise research on the impact of physician assistants/associates (PA) in secondary care, specifically acute internal medicine, care of the elderly, emergency medicine, trauma and orthopaedics, and mental health. Design: Systematic review. Setting: Electronic databases (Medline, Embase, ASSIA, CINAHL, SCOPUS, PsycINFO, Social Policy and Practice, EconLit and Cochrane), reference lists and related articles. Included articles: Peer-reviewed articles of any study design, published in English, 1995–2017. Interventions: Blinded parallel processes were used to screen abstracts and full text, data extractions and quality assessments against published guidelines. A narrative synthesis was undertaken. Outcome measures: Impact on: patients' experiences and outcomes, service organisation, working practices, other professional groups and costs. Results: 5472 references were identified and 161 read in full; 16 were included—emergency medicine (7), trauma and orthopaedics (6), acute internal medicine (2), mental health (1) and care of the elderly (0). All studies were observational, with variable methodological quality. In emergency medicine and in trauma and orthopaedics, when PAs are added to teams, reduced waiting and process times, lower charges, equivalent readmission rate and good acceptability to staff and patients are reported. Analgesia prescribing, operative complications and mortality outcomes were variable. In internal medicine outcomes of care provided by PAs and doctors were equivalent. Conclusions: PAs have been deployed to increase the capacity of a team, enabling gains in waiting time, throughput, continuity and medical cover. When PAs were compared with medical staff, reassuringly there was little or no negative effect on health outcomes or cost. The difficulty of attributing cause and effect in complex systems where work is organised in teams is highlighted. Further rigorous evaluation is required to address the complexity of the PA role, reporting on more than one setting, and including comparison between PAs and roles for which they are substituting. PROSPERO registration number: CRD42016032895.